2003
DOI: 10.1258/jrsm.96.9.449
|View full text |Cite
|
Sign up to set email alerts
|

Troubles with the foreskin: one hundred consecutive referrals to paediatric surgeons

Abstract: SUMMARYTo assess the reasons for and outcomes of referrals concerning the foreskin, 100 consecutive patients seen in paediatric clinics were followed to discharge.18 referrals were for circumcision on religious grounds. Of the other 82, the main reason for referral was nonretractability or phimosis. At clinic, 24 (29%) of these were deemed normal for age, 31 (38%) were treated with topical steroid (successfully in 25), 9 (11%) were listed for preputioplasty, 7 (9%) were listed for adhesiolysis, 7 (9%) were lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…[ 82 ] In contrast to a reported rate of 1%,[ 83 ] two UK studies found LS prevalence of 5% and 6% in uncircumcised boys under 18 and 15 years of age, respectively. [ 84 85 ] Histological examination of foreskins removed for various reasons revealed LS in 3.6%–19%. [ 86 87 88 89 90 91 ] A study in Plymouth, UK, of 422 boys aged 3 months to 16 years (mean 6 years) referred to a pediatric general surgical outpatient department with foreskin problems found 55.9% were normal, with the remainder (44.1%) undergoing surgery: 35% circumcision, 8% preputial adhesiolysis, and 0.1% frenuloplasty.…”
Section: Resultsmentioning
confidence: 99%
“…[ 82 ] In contrast to a reported rate of 1%,[ 83 ] two UK studies found LS prevalence of 5% and 6% in uncircumcised boys under 18 and 15 years of age, respectively. [ 84 85 ] Histological examination of foreskins removed for various reasons revealed LS in 3.6%–19%. [ 86 87 88 89 90 91 ] A study in Plymouth, UK, of 422 boys aged 3 months to 16 years (mean 6 years) referred to a pediatric general surgical outpatient department with foreskin problems found 55.9% were normal, with the remainder (44.1%) undergoing surgery: 35% circumcision, 8% preputial adhesiolysis, and 0.1% frenuloplasty.…”
Section: Resultsmentioning
confidence: 99%
“…It remains the case, however, that far more circumcisions are being prescribed than are actually justified by the presence of disease [31][32][33][34][35][36]. Since surgical interventions should only be performed when clinically necessary, especially in children [37], it seems appropriate for those of us who set ourselves up as medical educators to propose a clinical protocol for prescribing circumcision.…”
Section: Acceptability Of Circumcisionmentioning
confidence: 99%
“…Circumcision is a very old procedure and has been widely practiced since ancient times [ 1 , 2 ]. However, it is a routine procedure in Muslim countries such as Iran [ 3 ].…”
Section: Introductionmentioning
confidence: 99%